A perspective on paper-based microfluidics: Current status and future trends - Li, Xu; Ballerini, David R.; Shen, Wei (Biomicrofluidics, 2012)
“Paper-based microfluidics” or “lab on paper,” as a burgeoning research field with its beginning in 2007, provides a novel system for fluid handling and fluid analysis for a variety of applications including health diagnostics, environmental monitoring as well as food quality testing. The reasons why paper becomes an attractive substrate for making microfluidic systems include: (1) it is a ubiquitous and extremely cheap cellulosic material; (2) it is compatible with many chemical/biochemical/medical applications; and (3) it transports liquids using capillary forces without the assistance of external forces. By building microfluidic channels on paper, liquid flow is confined within the channels, and therefore, liquid flow can be guided in a controlled manner. A variety of 2D and even 3D microfluidic channels have been created on paper, which are able to transport liquids in the predesigned pathways on paper. At the current stage of its development, paper-based microfluidic system is claimed to be low-cost, easy-to-use, disposable, and equipment-free, and therefore, is a rising technology particularly relevant to improving the healthcare and disease screening in the developing world, especially for those areas with no- or low-infrastructure and limited trained medical and health professionals. The research in paper-based microfluidics is experiencing a period of explosion; most published works have focused on: (1) inventing low-cost and simple fabrication techniques for paper-based microfluidic devices; and (2) exploring new applications of paper-based microfluidics by incorporating efficient detection methods. This paper aims to review both the fabrication techniques and applications of paper-based microfluidics reported to date. This paper also attempts to convey to the readers, from the authors’ point of view the current limitations of paper-based microfluidics which require further research, and a few perspective directions this new analytical system may take in its development.